VCAM-1 on Peritoneum and α4β1 Integrin in Endometrium and Their Implications in Endometriosis. (January 2015) - Schutt, Amy K.; Atkins, Kristen A.; Slack-Davis, Jill K.; Stovall, Dale W.
<x xml:space="preserve">Abstract</x> The objective of the study is to investigate vascular cellular adhesion molecule-1 (VCAM-1) expression on peritoneal mesothelial cells and α4β1 integrin on eutopic endometrium as possible mechanisms in the pathogenesis of endometriosis. It is a case-control study carried out at an academic medical center. Participants are patients with (n=9) and without (n=15) endometriosis. The main outcome measures included VCAM-1 expression on peritoneal mesothelial cells and α4β1 expression on eutopic endometrium using immunohistochemistry and flow cytometry, respectively. Patients with endometriosis were more likely to express VCAM-1 on peritoneal mesothelial cells, both in areas with and without macroscopic disease, compared with patients without endometriosis (9/9 vs. 3/15, P<0.001). No differences were found between cases and controls in regards to eutopic endometrial expression of α4β1 integrin. The presence of VCAM-1 on peritoneal mesothelial cells is associated with endometriosis. This field effect, in addition to the similarity found with regards to the expression of α4β1 integrin in eutopic endometrium between cases and controls, may implicate the expression of VCAM-1 in the peritoneum, and not changes in the eutopic endometrium, as a contributor to the pathogenesis of endometriosis.